The Implementation of Marketing Mix as a Marketing Strategy for Pesantren-Based Educational Services - Sri Nurhasana (Program Studi Ekonomi Syariah, Fakultas Ekonomi dan Bisnis Islam, Universitas Al Hikmah Indonesia, 2024)
This study examines the marketing strategies applied in marketing educational services at Islamic boarding school-based educational institutions. This study is motivated by efforts to develop the quality of Islamic boarding school-based educational institutions, so that they are able to compete with other institutions. Marketing of educational services is intended to create conducive and stable marketing conditions, so as to provide a positive impact on the parties involved in the marketing process (both Islamic boarding schools as producers and the community as consumers). Based on the results of research conducted at the Zainul Hasan Genggong Model Islamic High School, it was found that Islamic boarding school-based educational institutions also apply various strategies in marketing their educational services. The marketing strategy at the Zainul Hasan Genggong Model Islamic High School is carried out through the application of 7P marketing mix theory (product, price, place, promotion, human resources, physical evidence, and process) by utilizing its superior competencies as an Islamic boarding school-based educational institution that tends to be based on students and achievements, so that it can target Muslim communities with both traditional and modern backgrounds as a marketing segment for its educational services.